1997
DOI: 10.1104/pp.113.2.535
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between Endoplasmic Reticulum-Type and Plasma Membrane-Type Ca2+ Pumps (Partial Purification of a 120-Kilodalton Ca2+-ATPase from Endomembranes)

Abstract: Two biochemical types of Ca2+-pumping ATPases were distinguished in membranes that were isolated from carrot (Daucus carota) suspension-cultured cells. One type hydrolyzed GTP nearly as well as ATP, was stimulated by calmodulin, and was resistant to cyclopiazonic acid. This plasma membrane (PM)-type pump was associated with PMs and endomembranes, including vacuolar membranes and the endoplasmic reticulum (ER). Another pump (“ER-type”) that was associated mainly with the ER hydrolyzed ATP preferentially, was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…5). Thus ECA1p resembled a carrot ER-associated Ca 2ϩ pump that was partially inhibited by CPA and insensitive to calmodulin (7). Preliminary results showed that ECA1p did not bind to calmodulin.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…5). Thus ECA1p resembled a carrot ER-associated Ca 2ϩ pump that was partially inhibited by CPA and insensitive to calmodulin (7). Preliminary results showed that ECA1p did not bind to calmodulin.…”
Section: Discussionmentioning
confidence: 87%
“…The PM-type pump is energized by GTP or ATP and is stimulated by calmodulin. This type of pump can be located on endomembranes, like the vacuole (6, 7), as well as the plasma membrane (7,8). Another pump is associated mainly with the ER.…”
Section: ؉mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the plant plasma membrane-localized pumps are also members of this structurally unique subfamily is not known. However, they are reported to be larger than ACA2p (110 kDa) and are closer to the 127-136-kDa size typical of an animal PM-type Ca 2ϩ pump (5,46,49). Thus, it remains an open question whether plant cells function with two distinct types of calmodulin regulated Ca 2ϩ pumps, or operate exclusively with variants of the subfamily described here.…”
Section: Ca 2ϩ -Atpase Isoform Aca2mentioning
confidence: 89%
“…Thus, cells require transport systems to carefully regulate Ca 2ϩ concentrations in different cellular compartments. In plants, high affinity Ca 2ϩ -translocating ATPases are thought to function in the endoplasmic reticulum, Golgi apparatus, tonoplast, plastid inner membrane, and plasma membrane (5)(6)(7)(8). In addition, plants have low affinity Ca 2ϩ /H ϩ antiporters (9).…”
Section: Calcium (Ca 2ϩmentioning
confidence: 99%